Legacy of the Last Glacial on the present-day distribution of deciduous versus evergreen boreal forests - Herzschuh, Ulrike (Prof. Dr.) (2018)
Issue Despite their rather similar climatic conditions, eastern Eurasia and northern North America are largely covered by different plant functional types (deciduous or evergreen boreal forest) composed of larch or pine, spruce and fir, respectively. I propose that these deciduous and evergreen boreal forests represent alternative quasi-stable states, triggered by their different northern tree refugia that reflect the different environmental conditions experienced during the Last Glacial. Evidence This view is supported by palaeoecological and environmental evidence. Once established, Asian larch forests are likely to have stabilized through a complex vegetation-fire-permafrost soil-climate feedback system. Conclusion With respect to future forest developments, this implies that Asian larch forests are likely to be governed by long-term trajectories and are therefore largely resistant to natural climate variability on time-scales shorter than millennia. The effects of regional human impact and anthropogenic global warming might, however, cause certain stability thresholds to be crossed, meaning that irreversible transitions occur and resulting in marked consequences for ecosystem services on these human-relevant time-scales.